Kinerja Pegawai Dinas Pemberdayaan Perempuan dan Perlindungan Anak dalam Penanganan Kasus Kekerasan Dalam Rumah Tangga di Sulawesi Utara - Guadalupe Simbolon; Devie S. R. Siwij; Brain Fransisco Supit (CV. Kurnia Grup, 2026)
This study examines employee performance at the Regional Women's Empowerment and Child Protection Service (DP3AD) of North Sulawesi Province in handling domestic violence (KDRT) cases. Fluctuating case resolution rates and unmet annual targets serve as the primary background of this research. The study aims to analyze performance across three dimensions, productivity, service quality, and responsibility, while identifying contributing factors. A descriptive qualitative method was employed through in-depth interviews, field observations, and documentation studies. Findings reveal that all three dimensions remain suboptimal: productivity is constrained by excessive workloads and limited human resources; service quality is hampered by delayed case handling, weak inter-unit coordination, and inconsistent SOP implementation; and employee responsibility requires strengthening through improved discipline and regulatory compliance. Competence, work motivation, managerial oversight, and organizational synergy were found to significantly influence overall performance. The study recommends periodic capacity-building programs, strengthened internal oversight mechanisms, and optimized cross-sector coordination to sustainably improve public service quality